4-Aminoquinoline as a privileged scaffold for the design of leishmanicidal agents: structure–property relationships and key biological targets - Romero, Angel H.; Delgado, Francisco (Frontiers in Chemistry, 2025)
Leishmaniasis is one of the most important neglected tropical diseases, with more than two million new cases annually. It is endemic in several regions worldwide, representing a public health problem for more than 88 countries, in particular in the tropical and subtropical regions of developing countries. At the moment, there are neither approved vaccines nor effective drugs for the treatment of human leishmaniasis for any of its three typical clinical manifestations, and, importantly, the drugs of clinical use have several side effects, require complex administration regimens, present high cost, and are ineffective in many populations due to pathogen resistance. Moreover, beyond the pharmacological exigencies, there are other challenges concerning its parasitic nature, such as its great genetic plasticity and adaptability, enabling it to activate a battery of genes to develop resistance quickly. All these aspects demand the identification and development of new, safe, and effective chemical systems, which must not only be focused on medicinal chemistry and pharmacological aspects but also consider key aspects relative to parasite survival.In this sense, the quinolines and, in particular, 4-aminoquinoline, represent a privileged scaffold for the design of potential leishmanicidal candidates due not only to their versatility to generate highly active and selective compounds but also to their correlation with well-defined biological targets. These facts make it possible to generate safe leishmanicidal agents targeted at key aspects of parasite survival.The current review summarizes the most current examples of leishmanicidal agents based on 4-aminoquinolines focusing the analysis on two essential aspects: (i) structure–property relationship to identify the key pharmacophores and (ii) mode of action focused on key targets in parasite survival (e.g., depolarization of potential mitochondrial, accumulation into macrophage lysosome, and immunostimulation of host cells). With that information, we seek to give useful guidelines for interested researchers to face the drug discovery and development process for selective and potent leishmanicidal agents based on 4-aminoquinolines.